DESIGN AND DEVELOP LOW-COST DEVICE FOR MONITORING OCCUPATIONAL NOISE EXPOSURE TOWARD WORKERS IN FACTORY - Mohd Azrin, Mohd Said; Ahmad Faridzul, Japar; Nor Kamaliana, Khamis; Abdullah, Yassin; Ana Sakura, Zainal Abidin; Rudiyanto, Philman Jong; Mohamad Syazwan Zafwan, Suffian; Aishah, Arsad (Publications International Lahore, Pakistan, 2020)
Occupational noiseexposure towards workeris amajorproblem related to health and safety. Itcan be annoying and affects the worker’s concentration and health during the working hours. Environmental stresssuch as occupational noise exposure from factories and industrial sites are well known with a harsh environment. This occupational noise pollutionsuch as heavy machinery noise, high number of large vehicles in and out of the sites which causing undesirable situation as a good working environment. However, the undesired noise exposure also will lead tocauses hazard and unhealthy environment at the workplace. Hence, this studydone as a solution for this problem where at least decreased the level of problems effect towardsworkers and increasethe company performance. The purpose of thisstudyis to design and develop low-cost device on monitoring occupational noise exposure named (LCDONE). This LCDONEconsist of programming for Arduino Wi-Fi UNO based ESPDuino-32 with integrated with IoTanalytics platform service ThingSpeak to gathered real time data monitoring. The data collection will be shown in decibel (dB)throughout the ThingSpeak Viewerand hasbeen validated with the established sound level meterRS PRO RS-95 with the average percentage of error for LCDONE from this study is 2.52%.The selected factory for this study and testing LCDONE was in Palm Oil Mill located in Kota Samarahan, Sarawak, Malaysia.